Integration of artificial intelligence and precision oncology in Latin America - Sussman, Liliana; Garcia-Robledo, Juan Esteban; Ordóñez-Reyes, Camila; Forero, Yency; Mosquera, Andrés F.; Ruíz-Patiño, Alejandro; Chamorro, Diego F.; Cardona, Andrés F. (Frontiers in Medical Technology, 2022)
Next-generation medicine encompasses different concepts related to healthcare models and technological developments. In Latin America and the Caribbean, healthcare systems are quite different between countries and it is also known that cancer control is insufficient and inefficient considering socioeconomically and geographical characteristics. Despite advancements in knowledge about the biology of the different oncological diseases, it continues to be a big challenge in terms of diagnosis, treatment, and prognosis for clinicians and researchers. With the development of molecular biology and diagnosis of therapeutic tools in the last years, artificial intelligence (AI) has become important, because it could improve different aspects like predicting clinically relevant parameters, cancer diagnosis, cancer research, and personalized medicine. In It is known that the incorporation of AI is being a big challenge in terms of diagnosis, treatment and prognosis for clinicians and researchers in cancer care. Therefore, some studies about AI in Latin American and the Caribbean are being conducted in the aim to improve performance of AI in those countries. This review is about the introduction of AI in cancer care in Latin America and the Caribbean, the advantages and promising results that it has shown and its current status in Latin America and the Caribbean.